2010
DOI: 10.2118/134247-pa
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Heavy Oil Recovery by Low Rate Waterflooding

Abstract: At the conclusion of primary heavy oil production, significant volumes of oil still remain in the reservoir under depleted reservoir pressure. Waterfloods are often considered for additional oil recovery. It is accepted that conventional oil waterflooding theory is not applicable for heavy oil. However, there is a lack of understanding of how waterfloods should perform in these reservoirs, particularly after water breakthrough. In this study, waterfloods were performed at multiple rates in cores containing hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…Despite the fact that some W/O emulsions were shown to have formed, and these are often indicative of an oil wet condition (Equation 1), the total water geometric mean T 2 values (T 2gm ) plotted in Figure 8 are still lower than the T 2gm of the original water-saturated core. This indicates that the rock was still water wet, and was verified through oil recovery via water imbibition 39 . Figure 9 shows the NMR spectra at the same four length locations after flooding one pore volume of DI AS solution through the core at a relatively high rate (0.51 m/day).…”
Section: Wettability Changes During As Floodingmentioning
confidence: 70%
See 2 more Smart Citations
“…Despite the fact that some W/O emulsions were shown to have formed, and these are often indicative of an oil wet condition (Equation 1), the total water geometric mean T 2 values (T 2gm ) plotted in Figure 8 are still lower than the T 2gm of the original water-saturated core. This indicates that the rock was still water wet, and was verified through oil recovery via water imbibition 39 . Figure 9 shows the NMR spectra at the same four length locations after flooding one pore volume of DI AS solution through the core at a relatively high rate (0.51 m/day).…”
Section: Wettability Changes During As Floodingmentioning
confidence: 70%
“…In fact, the optimal oil recoveries were around 70% of OOIP, and most floods actually recovered less oil. Under very low rate waterflooding for many pore volumes 3,39 , it is also possible to achieve similar residual oil saturation by allowing water imbibition to slowly sweep oil from the core. Therefore, as also observed previously by Jennings et al 24 , the improved oil response is one of improved sweep and accelerated oil production.…”
Section: Oil Recovery Through DI As Injection At Various Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…( and alkali, 8-14 low-rate waterflooding, 15 variable-rate waterflooding, 16 immiscible CO 2 flooding, 17 miscible CO 2 flooding, 18 and water-alternating-CO 2 injection. 10, 19,20 Among the suggested methods, a miscible gas injection process and, in particular, VAPEX suffers from low initial production rates, premature breakthrough, and possible formation damage due to in situ deasphalting.…”
Section: Introductionmentioning
confidence: 99%
“…Torabi et al [42] predicted heavy oil/water relative permeability by modified Corey-based correlations. Mai [43] reported that Johnson-Bossler-Naumann (JBN) method allowed for the calculation of apparent relative permeability curves that could be incorporated into reservoir simulators, and the effect of oil viscosity could be addressed through its effect on the apparent relative permeabilities calculated. Doorwar et al [44] considered that relative permeability functions needed to be modified to simulate unstable displacements with conventional simulators, and high viscosity ratio led to viscous fingering, which affected the observed relative permeability curves; they developed a lumped-finger model to modify multiphase flow equations and to yield pseudo relative permeability functions that accounted for viscous fingering.…”
mentioning
confidence: 99%